Pengaruh Online Customer Review dan Rating Media Online Shopee terhadap Minat Beli Konsumen Brand Erigo - Muhamad Reza Mauli; Zulfebriges (UNISBA Press, 2022)
Abstract. In times like this, access to information is very necessary, without world information such as stopping to look for information related to things of daily needs such as clothing, food and shelter in an era like this Online Media seems to be a necessity that is close to humans. Because all related information is displayed on online media, online media such as directions on a trip, we can find out a lot of information every day. Starting from shopping online in times like this, such as E-commerce that is present like Shopee, we can find out a lot of information related to the products we want to buy. The Review and Rating features in Shopee's E-commerce have also been applied in many other E-commerce, because it seems important and interesting for potential consumers in determining product purchases, because we can share information about goods or subjects such as Brand Erigo which working in the clothing line world where researchers want to prove by conducting a study entitled